Detekce sentinelových uzlin u karcinomu vulvy--metody a technika - Rob, L; Robová, H; Pluta, M; Strnad, P; Kacírek, J; Chmel, R; Teslík, L; Skapa, P; Táborská, K (Ceska gynekologie, 2006)
OBJECTIVE: To evaluate detection of sentinel lymph nodes (SLN) in squamous vulvar cancer with blue dye and 99mTc. The study describes technique of application, timing, management, detection rate (DR), specific side detection rate (SSDR) and false negative rate. DESIGN: Prospective clinical study. SETTING: Department of Obstetrics and Gynecology, Charles University Prague, 2nd Medical Faculty, Teaching Hospital Motol. PATIENTS AND METHODS: 46 women with squamous cell carcinoma tumors stage I or II, <4 cm with no clinical suspect lymph nodes were included. Blue dye alone was used in 16 women and the combination of 99mTc and blue dye was used in 30 women. Radiocoloid 99mTc was applied 3-5 hours and blue dye 3-5 minutes prior to ingvinal incision. RESULTS: We detected 88 SLN in 61 inguinal spaces. The detection rate in the blue dye group was 68.8 % (11 cases). One false negative SLN (6.3 %) appeared in this group. In blue dye+ 99mTc group detection rate was 100 % with no false negative SLN. CONCLUSION: Detection of SLN in squamous vulvar cancer with the combination of 99mTc and blue dye was statistically significantly more effective than using the blue dye alone.
Keywords: Lymphatic Metastasis; nádory vulvy; senioři; senioři nad 80 let; rosanilinová barviva; Vulvar Neoplasms; Female; Humans; Sentinel Lymph Node Biopsy; barvicí látky; Technetium Tc 99m Aggregated Albumin; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Carcinoma, Squamous Cell; Radiopharmaceuticals; falešně negativní reakce; Aged, 80 and over; biopsie sentinelové lymfatické uzliny; spinocelulární karcinom; radiofarmaka; Coloring Agents; dospělí; False Negative Reactions; Adult; lymfatické metastázy; Aged; Rosaniline Dyes; technecium 99mTc-agregovaný albumin